PSM-Mec—A Virulence Determinant that Connects Transcriptional Regulation, Virulence, and Antibiotic Resistance in Staphylococci - Qin, Li; McCausland, Joshua W.; Cheung, Gordon Y. C.; Otto, Michael (Frontiers in Microbiology, 2016)
PSM-mec is a secreted virulence factor that belongs to the phenol-soluble modulin (PSM) family of amphipathic, alpha-helical peptide toxins produced by Staphylococcus species. All known PSMs are core genome-encoded with the exception of PSM-mec, whose gene is found in specific sub-types of SCCmec methicillin resistance mobile genetic elements present in methicillin-resistant Staphylococcus aureus and coagulase-negative staphylococci. In addition to the cytolytic translational product, PSM-mec, the psm-mec locus encodes a regulatory RNA. In S. aureus, the psm-mec locus influences cytolytic capacity, methicillin resistance, biofilm formation, cell spreading and the expression of other virulence factors, such as other PSMs, which results in a significant impact on immune evasion and disease. However, these effects are highly strain-dependent, which is possibly due to differences in PSM-mec peptide versus psm-mec RNA-controlled effects. Here, we summarize the functional properties of PSM-mec and the psm-mec RNA molecule and their roles in staphylococcal pathogenesis and physiology.